Chain Conditions on Semirings - T. K. Mukherjee; M. K. Sen; Shamik Ghosh (International Journal of Mathematics and Mathematical Sciences)
In this paper we characterize the class of semirings S for which the semirings of square matrices Mn(S) over S are (left) k-artinian. Also an analogue of the Hilbert basis theorem for semirings is obtained.